2011
DOI: 10.3171/2010.9.spine09920
|View full text |Cite
|
Sign up to set email alerts
|

The role of adjuvant radiation therapy in the treatment of spinal myxopapillary ependymomas

Abstract: Object The goal in this study was to determine the role of radiation therapy (RT) in the treatment of spinal myxopapillary ependymomas (MPEs). Methods Thirty-seven patients with histologically verified spinal MPEs were reviewed. Kaplan-Meier analyses and Cox proportional hazard regression were used to determine what patient and treatment factors influenced overall survival (OS) and recurrence. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 9 publications
2
24
1
Order By: Relevance
“…7,33,57,62,67,70,74,80,87,93,117,118,129,133,139 However, Akyurek and colleagues 4 reported that in 35 cases of myxopapillary ependymomas, postoperative radiotherapy was able to decrease the rate of tumor progression, regardless of the extent of resection. In addition, Chao and colleagues 21 demonstrated that at the time of initial recurrence, radiation may be able to prolong the interval until subsequent recurrences. Given the rate of recurrence for spinal ependymomas treated with surgery alone and the success of radiation as a potential salvage therapy, Al-Halabi and colleagues 5 recommended that postoperative serial imaging be mandatory.…”
Section: Radiotherapymentioning
confidence: 99%
“…7,33,57,62,67,70,74,80,87,93,117,118,129,133,139 However, Akyurek and colleagues 4 reported that in 35 cases of myxopapillary ependymomas, postoperative radiotherapy was able to decrease the rate of tumor progression, regardless of the extent of resection. In addition, Chao and colleagues 21 demonstrated that at the time of initial recurrence, radiation may be able to prolong the interval until subsequent recurrences. Given the rate of recurrence for spinal ependymomas treated with surgery alone and the success of radiation as a potential salvage therapy, Al-Halabi and colleagues 5 recommended that postoperative serial imaging be mandatory.…”
Section: Radiotherapymentioning
confidence: 99%
“…Bagley and colleagues 7 and Chao and colleagues 11 demonstrated no benefit in recurrence-free survival for patients treated with adjuvant radiotherapy after surgery. Akyurek and colleagues, 2 on the other hand, found that adjuvant radiotherapy was associated with better outcomes for both patients who underwent GTR and those who underwent STR.…”
Section: ©Aans 2013mentioning
confidence: 99%
“…1,6,16,23,[27][28][29]32 In total, 28 articles with 475 patients were included in this integrative analysis. [2][3][4][5][7][8][9][10][11][12][13][14][15][17][18][19][20][21][23][24][25][26]30,31,[34][35][36][37] …”
Section: Article Selectionmentioning
confidence: 99%
“…An association between GTR and increased OS and PFS in cases of spinal ependymoma has been well documented in the adult literature and in a handful of pediatric studies; however, few studies provide analysis stratified by grade. 11,12,14,16,17,59,62 Safaee et al reported that among 43 Grade II ependymomas, GTR was associated with increased PFS. 59 Benesch et al (n = 29) did not find a statistically significant relationship between extent of resection and OS; however, they found that GTR trended toward an association with increased PFS (p = 0.088).…”
Section: Surgery and Adjuvant Radiation Therapymentioning
confidence: 99%